Career choices, career related stress and need for career counselling and guidance among young secondary school students: a cross-sectional study - Ain, Syed Najmul; Gilani, Mohamad Azhar; Lone, Kouser Sideeq (International Journal of Research in Medical Sciences, 2021)
Background: Career is one of the factors that determine the future of an individual. Vocational dimension is an important one which may influence the health of a person. The objective of this study was to find out the career choices among secondary school students in district Baramulla of the Kashmir valley and to find out the career related self-reported stress among the students. Methods: It was a cross-sectional study carried out in 2018 for a period of one month. A self-administered pre-designed questionnaire was distributed among students of class 9th and 10th availing tuitions from a private tuition centre. The information was collected regarding the socio-demographic characteristics, career choices, other information related to career, and self-reported career related stress. The data was entered in Microsoft excel 2010 and analysed using SPSS version 23. Results: A total of 100 students participated. Mean age of the students was 15.19±0.84 years with 57% females. Ninety seven percent of the students had been thinking about their career for quite some time. Most of the students wanted to pursue MBBS (52%) followed by engineering (14%). Seventy-four percent of the students were of the opinion that career counselling was necessary. Nineteen percent of students were stressed about their career. Conclusions: Most of the students had already decided on their career but many were stressed and unsure about what path to choose. About 74% of the students were of the opinion that there should be career counselling and guidance available for the students so that they are able to take the right decisions at the right time.